Giant virus with a remarkable complement of genes infects marine zooplankton - Fischer, Matthias G; Allen, Michael J; Wilson, William H; Suttle, Curtis A (Proceedings of the National Academy of Sciences - PNAS, 2010)
As major consumers of heterotrophic bacteria and phytoplankton, microzooplankton are a critical link in aquatic foodwebs. Here, we show that a major marine microflagellate grazer is infected by a giant virus, Cafeteria roenbergensis virus (CroV), which has the largest genome of any described marine virus (≈730 kb of double-stranded DNA). The central 618-kb coding part of this AT-rich genome contains 544 predicted protein-coding genes; putative early and late promoter motifs have been detected and assigned to 191 and 72 of them, respectively, and at least 274 genes were expressed during infection. The diverse coding potential of CroV includes predicted translation factors, DNA repair enzymes such as DNA mismatch repair protein MutS and two photolyases, multiple ubiquitin pathway components, four intein elements, and 22 tRNAs. Many genes including isoleucyl-tRNA synthetase, eIF-2γ, and an Elp3-like histone acetyltransferase are usually not found in viruses. We also discovered a 38-kb genomic region of putative bacterial origin, which encodes several predicted carbohydrate metabolizing enzymes, including an entire pathway for the biosynthesis of 3-deoxy-d-manno-octulosonate, a key component of the outer membrane in Gram-negative bacteria. Phylogenetic analysis indicates that CroV is a nucleocytoplasmic large DNA virus, with Acanthamoeba polyphaga mimivirus as its closest relative, although less than one-third of the genes of CroV have homologs in Mimivirus. CroV is a highly complex marine virus and the only virus studied in genetic detail that infects one of the major groups of predators in the oceans.